(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Survey knowledge and practice on colorectal cancer prevention in Khmer people aged 40 years and older in Tra Vinh province in 2020. Methods: Descriptive cross-sectional research design, direct interviews with 1,843 Khmer people selected by systematic random method in 30 communes of Tra Vinh province. Results: Knowledge about signs suggesting colorectal cancer was 17.8%, about risk factors for the disease was 14.1%, about prevention methods was 14.5% and about disease screening was 14.2%. The rate of correct general knowledge about colorectal cancer prevention is only 10.8%. The rate of current smokers is 17.4%; alcohol abuse is 7.3%; 53.0% of physical activity regimens meet recommendations, 15.9% of people eat enough fruits and vegetables; regularly eat red meat 13.8%; regularly eating processed foods such as fried/stir-fried is 14.4% and regularly eating grilled meat is 4.8%. The general rate of correct practice in colorectal cancer prevention is only 9.5%. Conclusions: Both knowledge and practice on colorectal cancer prevention in Khmer people is limited. Therefore, solutions for communication and health education suitable to the culture of the Khmer community are very necessary in the current period.